2018
DOI: 10.1039/c7cp08621k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of UV radiation damage in air on polymer film thickness, studied by soft X-ray spectromicroscopy

Abstract: The thicknesses of thin films of polystyrene (PS), poly(methyl methacrylate) (PMMA), and perfluorosulfonic acid (PFSA) were measured by Ultraviolet Spectral Reflectance (UV-SR) and Scanning Transmission X-ray Microscopy (STXM). At high doses, the UV irradiation in air used in the UV-SR method was found to modify the chemical structures of PS and PMMA (but not PFSA), leading to thinning of these polymer films. The chemical changes caused by UV/air radiation damage were characterized by STXM. When UV and X-ray r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The OD spectrum is related to the sample properties: OD­( x , y , E ) = μ­( E ) ρ t ( x , y ), where μ­( E ) is the mass absorption coefficient at energy E , ρ is the density, and t ( x , y ) is the thickness of the sample at the ( x , y ) pixel. The spin-coated PFSA film was 50(5) nm thick, as measured by X-ray absorption. , It was uniformly thick to <10 nm over a macroscopically large area (>0.1 × 0.1 mm).…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…The OD spectrum is related to the sample properties: OD­( x , y , E ) = μ­( E ) ρ t ( x , y ), where μ­( E ) is the mass absorption coefficient at energy E , ρ is the density, and t ( x , y ) is the thickness of the sample at the ( x , y ) pixel. The spin-coated PFSA film was 50(5) nm thick, as measured by X-ray absorption. , It was uniformly thick to <10 nm over a macroscopically large area (>0.1 × 0.1 mm).…”
Section: Methodsmentioning
confidence: 95%
“…The spin-coated PFSA film was 50(5) nm thick, as measured by X-ray absorption. 13,41 It was uniformly thick to <10 nm over a macroscopically large area (>0.1 × 0.1 mm).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, STXM was successfully employed in studying the changes in the polymer film thickness that are spincoated as tens of nanometers thick layers. 500 Although this high-end X-ray imaging example still mainly relies on synchrotron facilities, there is a promising development without synchrotron facilities as well. For instance, Sensini et al characterized sub-micron-wide electrospun fibers made of nylon, PLLA, and PLLA−collagen using high-resolution X-ray tomography (XCT).…”
Section: High-resolution X-ray Imagingmentioning
confidence: 99%
“…They demonstrated that STXM was able to distinguish a core diameter and thickness of 40–50 nm, which is otherwise not possible with conventional SEM or TEM techniques. Similarly, STXM was successfully employed in studying the changes in the polymer film thickness that are spincoated as tens of nanometers thick layers . Although this high-end X-ray imaging example still mainly relies on synchrotron facilities, there is a promising development without synchrotron facilities as well.…”
Section: Emerging Techniques For the Surface-sensitive Characterizationmentioning
confidence: 99%
“…Different rates of depletion of polymer coatings are reported to be linked to surface or bulk driven photo-chemical erosion. The initial rate of material erosion is reported to be constant and non-specific to two polymers studied by Melo et al [16].According to Tator [17], polyurethane resins are transparent to short wave UV radiations and they allow them to pass through with very little molecular absorption. Kim et al [18] reported that long term natural weathering on historical monuments degraded the lignin linearly from the surface.…”
Section: The Effect Of Bleaching On the Film Thickness (Ft)mentioning
confidence: 99%